Converting Disaster Experience into a Safer Built Environment : The Case of Japan - World Bank (World Bank, Tokyo, 2018)
Globally, up to 1.4 million people are moving into urban areas per week, and estimates indicate that nearly 1 billion new dwelling units will be built by 2050 to support this growing population. The way we build our cities today directly impacts the safety of future generations. Building code and regulation have proven to be cost-effective tools to promote healthy, safe sand resilient cities. Japan’s effective use of building regulations to reduce risk is a compelling success story and provides a number of relevant lessons for low- and middle-income countries. Japan has proven that effective disaster risk reduction is possible, even in the face of highly destructive disasters. Among other measures, its building regulations have played a crucial role.